The Barbed-Wire College : Reeducating German POWs in the United States During World War II. - Robin, Ron Theodore (Princeton University Press, 2001)
From Stalag 17 to The Manchurian Candidate, the American media have long been fascinated with stories of American prisoners of war. But few Americans are aware that enemy prisoners of war were incarcerated on our own soil during World War II. In The Barbed-Wire College Ron Robin tells the extraordinary story of the 380,000 German prisoners who filled camps from Rhode Island to Wisconsin, Missouri to New Jersey. Using personal narratives, camp newspapers, and military records, Robin re-creates in arresting detail the attempts of prison officials to mold the daily lives and minds of their prison.